Variación temporal y espacial de aves playeras en la laguna Barra de Navidad, Jalisco, en tres temporadas no reproductivas - Hernández, Salvador (2012)
Temporal and spatial variation of shorebirds in Barra de Navidad lagoon, Jalisco, during three non-breeding seasons. Resident and migratory shorebirds inhabit different kinds of wetlands such as lagoons, rivers and seashores among others. In recent years, these areas have been importantly affected by urban, agriculture and touristic activities, such as the Barra de Navidad lagoon, for which little information is available to support conservation programs. The aim of this work was to describe shorebirds temporal and spatial distribution in Barra de Navidad lagoon during three non-breeding seasons (1999-2000, 2006-2007 and 2008-2009). For this, monthly censuses were performed from November-April with the purpose of registering all the shorebirds species. We were able to identify 19 shorebirds species (three residents and 16 winter visitors), of which Charadrius wilsonia, Limosa fedoa and Tringa semipalmata were the most abundant. The greater number of species was registered for November, December and March of the first and third seasons. The greater number of individuals was registered when birds were feeding during low tides, mainly in December, January and February of the first and third seasons. At low tide, there was a great number of species and individuals in zone C. This area had muddy substrates that were exposed during low tides and were used to feed. Barra de Navidad lagoon provided suitable habitats for feeding and resting for resident and migratory birds. Twelve of the 19 species were considered as priority within the Mexican bird conservation strategy. However, these habitats are threatened by human activities performed in the nearby areas of the lagoon that may have negative consequences for the distribution, abundance and conservation of these species.